Pay it forward: Impacts of a rural livelihoods program with built-in spillovers - Janzen, Sarah A.; Magnan, Nicholas; Sharma, Sudhindra; Thompson, William M. (Agricultural and Applied Economics Association, 2021)
We evaluate 2.5-3.5 year impacts of a livelihoods program using an RCT in Nepal. The program targets women and employs self-help groups, livestock transfers, and trainings. We assigned three variations of the program: full benefits, no livestock, and no values-based training, which includes encouragement to “pay it forward” (PIF) by training and giving livestock to others. With this encouragement in mind, the study is uniquely designed to evaluate the program’s ability to generate intentional spillover (PIF) effects. We observe impacts for direct beneficiaries in line with outcomes directly targeted by the intervention - beneficiaries have bigger herds, improved livestock practices, more goat sales and higher profit from goat production. In addition, women are more empowered and have greater financial inclusion. The asset transfer increases program costs, but there is weak evidence suggestive of an independent marginal impact. We observe strong PIF spillover effects, with important implications for cost effectiveness.